Community Empowerment Through Pkk Harjosari I Medan Namely The Utilization Of Separated White Waste Into Dish Soap - Asnawi, Asnawi; Siregar, Nurhafni; Sidabutar, Fini Yanti; Frandika, Frandika; Hasarah, Hasarah; Tanjung, Herni Savana Br; Ahya, Ismiati; Sirait, Luciyana Br (International Journal of Community Service (IJCS), 2025)
Banana trees are known as highly beneficial plants because almost all of their parts can be used for various purposes, including processed foods. However, many people are still unaware that besides the fruit, heart, and leaves, other parts such as the stem, stump, and even the banana peel can also be utilized. Most people only use the commonly used parts of the banana. However, banana peels have great potential, such as being used as dish soap. Banana peels contain compounds like saponins (foaming agents), tannins, and flavonoids, which have antibacterial properties, making them suitable as a soap base.This community service activity was conducted in Harjosari 1, Medan, using outreach methods and hands-on practice in making dish soap from banana peels with local residents. The success of this activity was measured by increased community understanding and successful home-made soap production, which was monitored regularly through a WhatsApp group